Effects of Multidrug-Resistant Organism Infection Control Simulation Program on the Infection Control Fatigue, Job Stress, and Performance of Nurses (Medico Legal Update, 2021)
Background: This study was conducted to develop a training program simulating multidrug-resistantorganism infection control for nurses and to verify its effectiveness.Method: This was a randomized, control-group, pretest-posttest design study carried out with a total ofthirty-one nurses. A general lecture on theories was provided to the control group, while the developedsimulation training program was implemented for the experimental group.Result: The results showed that the experimental group who received the multidrug-resistant infectioncontrol simulation training program recorded higher infection control performance than the control groupwho received lecture-based training (p=.029). However, there was no statistically significant difference ininfection control fatigue and job stress between the two groups.Conclusion: It was found that the simulation training program is an effective intervention that can improvethe performance of infection control. Repeated research on diverse variables is necessary in the future inorder to continuously measure the effectiveness of the simulation training program.